Akuntansi Hijau: Konsep dan Perspektif Maqashid Syariah - Ridho Erianto; Indra Mualim Hasibuan; Nurlaila Nurlaila (Department of Accounting, Faculty of Economics & Business, 2023)
Profit oriented is the core of conventional accounting concepts and ignores profit oriented which has implications for environmental pollution. The phenomenon of environmental issues is increasingly interesting to study and is the basis for the birth of a new accounting paradigm, namely Green Accounting. Green accounting principles are in line with Islamic teachings contained in the sharia maqashid theory. This study aims to describe the concept of green accounting and green accounting in terms of maqashid sharia theory. This study uses a qualitative approach to the analysis of literature studies using data collection techniques in the form of documentation. The results of green accounting research contain guidelines for companies in compiling financial reports by including social and environmental responsibility cost components in their financial reports. Judging from the theory of maqashid sharia, the concept of green accounting has the same goal as maqashid sharia, namely protecting religion, protecting the soul, protecting the mind, protecting offspring, and protecting property.